2020
DOI: 10.1111/1742-6723.13641
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Canadian Syncope Risk Score for patients presenting with undifferentiated syncope to the emergency department

Abstract: Objective To validate the accuracy and safety of the Canadian Syncope Risk Score (CSRS) for patients presenting with syncope. Methods Single centre prospective observational study in Brisbane, Australia. Adults presenting to the ED with syncope within the last 24 h were recruited after applying exclusion criteria. Study was conducted over 1 year, from March 2018 to March 2019. Thirty‐day serious adverse events (SAE) were reported based on the original derivation study and standardised outcome reporting for syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…In other hand, there were 141 (49.8%) very-low-risk, 62 (21.9%) low-risk, 61 (21.6%) medium-risk, 12 (4.2%) high-risk and 7 (2.5%) very-high-risk patients identified in Chan et al, 2020 study. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other hand, there were 141 (49.8%) very-low-risk, 62 (21.9%) low-risk, 61 (21.6%) medium-risk, 12 (4.2%) high-risk and 7 (2.5%) very-high-risk patients identified in Chan et al, 2020 study. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…The CSRS performed with the same sensitivity for a threshold score of 1 or higher but with higher specificity of 72.8%. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…The model had a 97.8% sensitivity and 44.3% specificity at a score of −1 or higher. An Australian single center validation study in 283 patients, however, demonstrated a lower sensitivity (71.4%) of a CSRS −1 [ 54 ]; similar sensitivity was maintained at a CSRS threshold of 1, with improved specificity (72.8%), and maintained a negative predictive value of 99%.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Notable examples include the San Francisco Syncope Rule (SFSR) 4 and the Canadian Syncope Risk Score (CSRS) 5 . These rules have displayed mixed results in external validation studies 6–9 . None of these rules have been widely adopted in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“… 5 These rules have displayed mixed results in external validation studies. 6 , 7 , 8 , 9 None of these rules have been widely adopted in clinical practice. Furthermore, guidelines for the management of syncope emphasize that existing risk scores should not be used alone for risk stratification because they have not performed better than unstructured clinical judgment.…”
Section: Introductionmentioning
confidence: 99%